MODERN MEDIATEXT: ITS ROLE IN THE LANGUAGE TRAINING OF THE BACHELORS - Larisa G. Lysytskaya (Высшее образование в России, 2016)
The article discusses the goals of the course «Speech Culture» in the context of formation of a competence model of a graduate and considers the modern mediatexts in the light of their impacting function and influence both on a general cultural and general professional training of bachelors of pedagogy and on the literary language in general.